KOINTEGRASI MODEL EKONOMI SEKTOR PERTANIAN INDONESIA (PENDEKTAN VAR DALAM DUAL ECONOMY MODEL) - DARSONO DARSONO (Universitas Sebelas Maret, 2007)
The indonesian's economy change was very dynamic still in development. Must be carefully for modeling in econometrics. The dual economy model with vector auto-regression (VAR) approach is answer's to sufficiency analytical needed at agricultural sector economic model analysis, so finding the co-integration variables in the modle. the research aim's to composing and comparing between structural VAR and co-integration approach in agricultural sector economic model, and finding the short and long run relation contribution of variables in the model